Beyond the philosopher's fear : a Cavellian reading of gender, origin and religion in modern skepticism - Viefhues-Bailey, Ludger H., 1965- (Intersections (Aldershot, England), 2007)
Based on a detailed analysis of gender in Stanley Cavell's treatment of the skeptical problem, this book addresses the relationship between gender and religion in modern skepticism. Engaging in dialogue with Julia Kristeva's philosophy, Viefhues claims that a religious problem underlies Cavell's understanding of the feminine.